Corrigendum to ‘Design of a red-emitter hybrid material for bioimaging: europium complexes grafted on silica particles’, (Materials Today Chemistry (2019) 14, (S2468519419302162), (10.1016/j.mtchem.2019.100204)) - Mutti, A. M.G. [UNESP]; Santos, J. A.O. [UNESP]; Cavalcante, D. G.S.M. [UNESP]; Gomes, A. S. [UNESP]; Job, A. E. [UNESP]; Teixeira, G. R. [UNESP]; Pires, A. M. [UNESP]; Lima, S. A.M. [UNESP] (Elsevier, 2020)
The authors regret for the title of Figure 9 been duplicated from Figure 8. The correct title for Figure 9 is as follows: ‘Fig. 9. Confocal laser scanning microscopy images of tissue sections of gastrocnemius muscle cells from rats exposed to 40 μg/mL suspension of SiO2-[Eu(SB)(dbm)y] for 12 hours, plus DAPI and FITC dyes using 40x of magnification, and lens aperture number of 0.95. (A) Excitation with 488 nm laser and reading on FITC channel - green; (B) excitation with the 561 nm laser and reading on the Texas Red channel - red; (C) overlapping images A and B; (D) image obtained under excitation with the 405 nm laser and reading on the blue DAPI channel and overlapping with images A and B. The authors would like to apologize for any inconvenience caused.